Encompassing monetary policy strategy review - Otmar Issing (Leibniz Institute for Financial Research SAFE, 2020)
This Policy White Paper assesses several main elements of ECB's upcoming review of its monetary policy strategy, announced in January 2020. Four aspects of the review are discussed in detail: i) ECB's definition of price stability and the arguments for and against inflation targeting; ii) the scope of ECB's objectives, considering financial stability, employment and the sustainability of the environment; iii) an update of ECB's economic and monetary analyses to assess the risks to price stability; iv) the ECB's communication practice. Furthermore, an overview of the ECB's monetary policy strategy and its last evaluation in 2003 is given.
Keywords: 330; monetary policy; ECB; price stability; two-pillar system; strategy review